Economic evaluation of sublingual vs subcutaneous allergen immunotherapy - Pokladnikova, Jitka; Krcmova, Irena; Vlcek, Jiri (Annals of allergy, asthma & immunology, 2008)
BACKGROUND: Sublingual allergen immunotherapy (SLIT) is a commonly used alternative route of administration to standard subcutaneous immunotherapy (SCIT) in Europe. Despite its wide use, the cost-effectiveness of SLIT vs SCIT has not been well established. OBJECTIVE: To evaluate the cost and effectiveness of SLIT compared with SCIT in patients with allergic rhinoconjunctivitis during a 3-year specific allergen immunotherapy (SIT) from a third-party payer's, a patient's, and society's perspectives. METHODS: We performed an open-label randomized clinical trial of patients receiving SLIT (n = 19), patients receiving SCIT (n = 23), and a control group (n = 22). The outcome measures were Rhinoconjunctivitis Quality of Life Questionnaire score, visual analog scale score, symptomatic medication reduction, and direct and indirect costs. RESULTS: SLIT offered clinical benefits to patients comparable to those provided by SCIT. From the perspective of a third-party payer, the total average direct medical cost per patient of 3-year SIT was estimated at Euro 416 vs Euro 482 in the SLIT and SCIT groups, respectively. A patient who received SLIT paid less than a patient who received SCIT for all out-of-pocket costs (Euro176 for SLIT vs Euro 255 for SCIT) but more for sole allergen extracts (Euro 72 for SLIT vs Euro 55 for SCIT). When both direct and indirect costs were considered, the 3-year SIT expenditures per patient reached Euro 684 vs Euro 1,004 in the SLIT and SCIT groups, respectively. CONCLUSIONS: SLIT represents a less expensive alternative relative to subcutaneous administration from all perspectives. However, from a patient's perspective, SCIT offers a less expensive alternative for patients who do not experience loss of income and travel costs associated with treatment.
Keywords: dospělí; sezónní alergická rýma; Female; aplikace sublinguální; Adult; výsledek terapie; Allergens; ženské pohlaví; rostlinné extrakty; lidé; injekce subkutánní; Administration, Sublingual; Treatment Outcome; Rhinitis, Allergic, Seasonal; Poaceae; Office Visits; Desensitization, Immunologic; Male; náklady a analýza nákladů; Czech Republic; lipnicovité; návštěvy v ordinaci; Injections, Subcutaneous; pyl; Pollen; Plant Extracts; Česká republika; alergeny; desenzibilizace imunologická; mužské pohlaví; Costs and Cost Analysis; Humans